Delivering Localism: The Critical Role of Trust and Collaboration. Issue 3 (10th April 2013) - Padley, Matt
<x content-type="archive" xml:space="preserve">Abstract</x> Debate regarding the relationship between individual and state has been prominent throughout the current UK government's term in office and localism has come to occupy a central role in current policy. This article argues that attempts to deliver this localist vision should focus on the critical role of social trust and that this is best developed through collaboration. The actions identified as necessary for delivering decentralisation are considered alongside a review of the view of localism articulated in Coalition policy. The article then explores collaboration and co-production as a means of strengthening social networks and delivering the promises of localism.